2020
DOI: 10.1007/s12264-020-00549-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Stress on Attention Control: Evidence from Behavioral and Event-Related Potential Analyses

Abstract: Chronic stress affects brain function, so assessing its hazards is important for mental health. To overcome the limitations of behavioral data, we combined behavioral and event-related potentials (ERPs) in an attention network task. This task allowed us to differentiate between three specific aspects of attention: alerting, orienting, and execution. Forty-one participants under chronic stress and 31 non-stressed participants were enrolled. On the performance level, the chronically stressed group showed a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 94 publications
(110 reference statements)
1
29
0
Order By: Relevance
“…For example, monitoring may be a function of working memory, instead of attention, as defined by Petersen and Posner (2012). Future studies may further investigate the association between chronic stress and attention monitoring, adding to the limited existing literature (e.g., Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, monitoring may be a function of working memory, instead of attention, as defined by Petersen and Posner (2012). Future studies may further investigate the association between chronic stress and attention monitoring, adding to the limited existing literature (e.g., Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has strong construct validity and reliability across gender, socioeconomic status, age groups, ethnicity, and other demographic characteristics (Cohen et al, 1983). The PSS is widely used in studies investigating chronic stress (e.g., Pompon et al, 2019) and is employed in one of the few existing studies of the association between monitoring and chronic stress (Liu et al, 2020).…”
Section: Chronic Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation for the current finding is that COVID-related stress placed an excessive demand on participants attentional capacity, which resulted in an impairment in recognition. In support of this explanation, research has revealed that stressors can significantly reduce attentional network capacity and attenuate performance on tasks that require continuous attention (Liu et al, 2020). This effect is typically produced as even mildly stressful events can increase glucocorticoid and monoaminergic release, which subsequently impairs the neuronal firing and cortical-connectivity of the pre-frontal cortex (PFC), an area of the brain associated with higher order cognitive functions, such as attention and memory (Arnsten, 2009).…”
Section: Discussionmentioning
confidence: 99%